2003
DOI: 10.1177/0148607103027006404
|View full text |Cite
|
Sign up to set email alerts
|

Oral glutamine (AES‐14) supplementation inhibits PI‐3k/Akt signaling in experimental breast cancer

Abstract: GLN supplementation inhibited the PI-3K/Akt pathway that is thought to be important in increasing cell survival during tumorigenesis. These results are in agreement with our hypothesis that GLN counteracts the effects of DMBA and blocks carcinogenesis in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
(39 reference statements)
2
10
0
Order By: Relevance
“…3, p85 PI3K-e; 805 ± 88 vs. 2,503 ± 193; P < 0.05). These results are consistent with our previously published data of inhibition of anti-apoptotic Akt signaling in mammary tissue of rats with experimental breast cancer (31).…”
Section: Effect Of Gln On Protein Expression Of P21 Waf1/cip1 Ptensupporting
confidence: 94%
See 3 more Smart Citations
“…3, p85 PI3K-e; 805 ± 88 vs. 2,503 ± 193; P < 0.05). These results are consistent with our previously published data of inhibition of anti-apoptotic Akt signaling in mammary tissue of rats with experimental breast cancer (31).…”
Section: Effect Of Gln On Protein Expression Of P21 Waf1/cip1 Ptensupporting
confidence: 94%
“…The results published elsewhere (22,31,34), showed that tumor development was significantly (P = 0.007, GLN vs. control, Fisher Exact Test) reduced by GLN supplementation at the end of the study (11 wk after DMBA application). The GLN-supplemented group had 50% less tumors in comparison with the control group (Fig.…”
Section: Effect Of Dietary Gln On Carcinogenicity Of Dmbamentioning
confidence: 73%
See 2 more Smart Citations
“…They found that a GLN enriched diet reduced tumor GSH-to-oxidized glutathione (GSSG) ratios, up-regulated Bax and caspase-3 expression and reduced Bcl-2 levels, essentially reducing the "apoptotic threshold" of the tumor. This same group also reported that GLN-enriched diets depressed insulin-like growth factor-1 (IGF1), its receptor (IGF1R) and PKB/Akt protein levels and enhanced Bad expression in breast tumors more than in normal tissues, again depressing survival signaling in cancerous tissue [138]. The mechanism by which GSH levels and anti-apoptotic signaling are selectively repressed by GLN-enriched diets in chemically induced fibrosarcoma and breast tumors is unclear, but the implication from this research thus far is that the reluctance to use GLN-enriched nutritional regimens in cancer patients may be unfounded.…”
Section: A Reductionist View: the Gln-glutathione Link In Cancer Cellsmentioning
confidence: 89%